Kontribusi Cukai Minuman Ber Alkohol Ke Indonesia terhadap Pendapatan Negara Tahun 2021-2023 (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the contribution of excise revenue from alcoholic beverages to Indonesia’s state revenue during the period 2021–2023. Alcoholic beverages are classified as excisable goods due to their potential negative impacts on public health and social order, making excise duty an important fiscal instrument for both revenue generation and consumption control. The objective of this research is to analyze the trend and magnitude of excise revenue from alcoholic beverages and its role in supporting national income. This study employs a quantitative descriptive method using secondary data obtained from official government publications, including reports from the Ministry of Finance and the Directorate General of Customs and Excise. The data are analyzed by comparing annual excise revenue figures and identifying their contribution to total excise and state revenue over the observed period. The findings indicate that excise revenue from alcoholic beverages showed a fluctuating but generally increasing trend from 2021 to 2023, reflecting post-pandemic economic recovery and adjustments in excise tariff policies. Despite its relatively smaller share compared to tobacco excise, alcoholic beverage excise consistently contributed to state revenue and demonstrated fiscal potential. The study implies that effective excise policy on alcoholic beverages can support state revenue while simultaneously serving as a regulatory tool to control consumption and mitigate social and health risks.